THE EFFECT OF EXPOSURE TO EXTREMELY LOW FREQUENCY MAGNETIC FIELDS ON TEMPE FERMENTATION - Arya Adhi Putrawan; Arindra, Annisa Dwi; Nanda, Robiatul Adawiyah Alfi; A.N, Nadiefa Nissa’ul; Yushardi, Yushardi; Anggraeni, Firdha Kusuma Ayu; Meilina, Ike Lusi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This study explores the novel effect of Extremely Low Frequency (ELF) magnetic field radiation on the ripening process of raw fermented tempe, a traditional Indonesian food made from soybeans. ELF magnetic fields are environmental factors that can influence the growth of microorganism activity. The study uses a unique laboratory experimental method that employs a Current Transformer (CT) device to produce an ELF magnetic field with an intensity of 500miu, which is a relatively high intensity compared to the natural background level of ELF magnetic field. The study examines 20 raw tempe samples, each weighing 100g, divided into two groups: a control group and an experimental group. The experimental group is exposed to the ELF magnetic field for 24 hours, while the control group is not. The study measures the changes in the microbial population, pH, moisture content, and sensory quality of the tempe samples after the exposure. The study aims to prove the effect of ELF magnetic field radiation on food security and to provide insights for the development of new food preservation techniques.